Travelling to Tourism Destinations through the lens of Sustainability: An extended TPB Model to predict behavioural intention of Gen Z Consumers - —, Sujood; Siddiqui, Samiha; Bano, Naseem; Hamid, Sheeba (Journal of Tourism, Sustainability and Well-being, 2022)
The aim of this study is to predict Gen Z Consumers’ behavioural intention towards travelling to tourism destinations in the context of sustainability by developing an integrated structural model that incorporates the Theory of Planned Behaviour model with the additional constructs i.e. climate change awareness and desire for digital disconnection. The data was collected using the online questionnaire developed with Google forms and examined using SEM with AMOS and SPSS software. The hypotheses were statistically tested and the results revealed that integrating the theory of planned behaviour with climate change awareness and desire for digital disconnection leads to a strong model for examining behavioural intentions towards visiting tourism destinations. The findings may be used by government agencies, tourist management departments, and tourism businesses to establish suitable tourism development policies in tourism destinations. To the best of the authors’ knowledge, this study is one the first in tourism research to integrate the theory of planned behaviour with climate change awareness and desire for digital disconnection to investigate Gen Z Consumers’ behavioural intention towards travelling to tourism destinations.